EnglishWhen Compassion Becomes a Threat: Reasons for Clients’ Resistance to Therapeutic Support - Gvozden, Matija (Engrami, 2026)
Compassion represents one of the most significant components of the therapeutic relationship. It can be defined as a basic caring attitude, involving deep awareness of one’s own and others’ suffering, accompanied by the desire and efforts to alleviate it. The aim of this paper is to examine the contributing factors and effective strategies for managing fears, psychological blocks, and resistances that prevent clients from receiving care and compassion from the therapist, approached primarily from the perspective of Compassion-Focused Therapy. The paper focuses on clients who have experienced childhood trauma and who therefore often struggle to receive or accept therapeutic support due to the deep impact of trauma on trust, attachment, and core beliefs about others. We will first discuss the concept of compassion, followed by an examination of the various barriers to its development, including clients’ beliefs that they do not deserve care and warmth, doubts about the therapist’s intentions, and fears of their own emotional vulnerability. We will also present strategies for overcoming fears, blocks and resistance to compassion, which include: developing a compassionate relationship within the therapeutic environment, psychoeducation on the function of compassion, working on beliefs that block compassion, cultivating physiological calmness and grounding in the present moment, compassionate imagination and working with shame and early developmental trauma. Understanding and validating resistance are not obstacles but essential parts of the therapeutic process, enabling the client to gradually develop the capacity and willingness to accept warmth and care from others. Working through resistance within therapy creates space for developing the ability to extend compassion to oneself and others, thereby improving emotional regulation.